Synaesthesia and cycling data art: towards cross-modal representations of self-tacking cycling data. Issue 2 (3rd April 2019) - O'Neill, Shaleph
ABSTRACT: This paper develops ideas around cycling as art practice. The questions at the heart of it revolve around how new data technologies enable us to represent such experiences as artworks. Recent research in neuroscience has begun to establish the ways in which modes of perception are processed in the brain. Related research suggests that Synaesthesia may be caused by a genetic mutation that results in a 'cross wiring' of these modes of perception. Within the arts there is a long history of exploration around synaesthesia, ideas that are becoming relevant again particularly in relation to the growth in personal data. Representing sensations and transferring them from one mode to another offers a way to handle some of this data and potentially say new things about our experiences. The author explores these ideas through artworks made using data from cycling to investigate the visualization of this experience.